2012
DOI: 10.1080/00071668.2012.702340
|View full text |Cite
|
Sign up to set email alerts
|

The effects of turmeric supplementation on antioxidant status, blood gas indices and mortality in broiler chickens with T3-induced ascites

Abstract: 1. A total of 320 one-day-old Ross male broiler chickens were used to investigate the effects of 0·0, 2·5, 5·0 and 7·5 g/kg turmeric rhizome powder (TRP) in the diet, on antioxidant status, biochemical gas indices and mortality in broiler chickens with triiodothyronine (T(3)) induced ascites. 2. The TRP supplementation had no effect on blood pH, pO(2) or pCO(2) during the whole period of study. Moreover, supplementation of TRP did not influence the heart weight, right ventricle, left ventricle, or total ventri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 35 publications
1
9
1
Order By: Relevance
“…The findings of the present study also demonstrated that dietary TRE supplementation could improve the antioxidant capacity of broilers by increasing SOD and GSH-Px activities and decreasing serum MDA concentrations in broilers. These results are in accordance with those of several reports of standard broilers (Daneshyar, 2012;Daneshyar et al, 2012).…”
Section: Antioxidant Capabilitysupporting
confidence: 93%
“…The findings of the present study also demonstrated that dietary TRE supplementation could improve the antioxidant capacity of broilers by increasing SOD and GSH-Px activities and decreasing serum MDA concentrations in broilers. These results are in accordance with those of several reports of standard broilers (Daneshyar, 2012;Daneshyar et al, 2012).…”
Section: Antioxidant Capabilitysupporting
confidence: 93%
“…However, the results of the current study regarding the higher meat TBARS content in 10 g/kg of sumac-fed birds conflict with those in Song et al's report, which may be related to a relatively intense oxidative stress in the current experiment owing to continuous heat stress. Daneshyar et al (2012) stated that inclusion of an antioxidant (turmeric rhizome powder) alone to the diets cannot improve the antioxidant defence system during intense oxidative stresses such as T 3 -induced ascites. The lower TBARS content of thigh meat in AT-fed birds of the current experiment is connected to the antioxidant ability of vitamin E. It is known that vitamin E is the first line of defence against lipid peroxidation.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, low availability of polyphenolic compounds for growing chickens, breeders and layers [112] is an important limiting factor of their biological efficacy and nutritive value. For example, there was no effect of dietary turmeric rhizome powder (0.25-0.75%) on the activities of GSH-Px and SOD in thigh muscle [113] or serum [114]. Feeding to broiler chicks diets enriched with selected herbal supplements failed to affect the growth performance of chickens at 42 days of age.…”
Section: Phytochemicalsmentioning
confidence: 99%